2016
DOI: 10.1007/s11192-016-2041-z
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-first century macro-trends in the institutional fabric of science: bibliometric monitoring and analysis

Abstract: Some say that world science has become more ‘applied’, or at least more ‘application-oriented’, in recent years. Replacing the ill-defined distinction between ‘basic research’ and ‘applied research’, we introduce ‘research application orientation’ domains as an alternative conceptual and analytical framework for examining research output growth patterns. To distinguish possible developmental trajectories we define three institutional domains: ‘university’, ‘industry’, ‘hospitals’. Our macro-level bibliometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Bibliometrics combined with visualized mapping has been recognized as an effective means of assessing scientific research trends regarding a specific field, both quantitatively and systematically [ 30 ]; they can also uncover directions of scientific research, as shown previously [ 22 , 31 ]. In this study, a gradual shift in terms of research focus from “characteristics” to “treatments and effects” was seen, which is in accordance with the rule of the development of the translational medicine; therefore, the scientific community appears to be interested in the therapeutic potential of UC-MSC research at present.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometrics combined with visualized mapping has been recognized as an effective means of assessing scientific research trends regarding a specific field, both quantitatively and systematically [ 30 ]; they can also uncover directions of scientific research, as shown previously [ 22 , 31 ]. In this study, a gradual shift in terms of research focus from “characteristics” to “treatments and effects” was seen, which is in accordance with the rule of the development of the translational medicine; therefore, the scientific community appears to be interested in the therapeutic potential of UC-MSC research at present.…”
Section: Discussionmentioning
confidence: 99%
“…Publication, as a central part of scienti c research, is a signi cant indicator for research contribution. Bibliometrics combined with visualized mapping has been recognized as an effective means of assessing scienti c progress [24,25] . Information from online literature databases and metrology characteristics were analyzed via bibliometric analysis, which can be used to quantitatively and qualitatively evaluate the trends in the research community over time [26] .…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometrics and visualized mapping may quantitatively monitor research performance in science and present predictions [ 25 ]. Bibliometric study has had impact on other scientific and professional communities.…”
Section: Discussionmentioning
confidence: 99%